Performance Indicators for Wireless Intelligent Sensors Applications - Saad Chakkor (Institute of Advanced Engineering and Science, 2014)
The metrology technology has been evolved so much with the wireless sensor intelligent systems providing more capabilities in term of processing, remote multi-sensing fusion and storage. This kind of systems can be used in many types of environments. The monitoring is one of the most used. However, various design challenges for wireless intelligent sensors systems are imposed to overcome the physical limitations. Communication in sensor network should be as efficient as possible, especially for applications requiring specific performances. This paper analyzes the performance indicators of the sensing devices systems which stand for superior measurement, more accuracy and reliability. Study findings prescribe researchers, developers/ engineers and users to realizing an enhanced sensing motes design strategy that offers operational advantages which can give cost-effective solutions for an application.